MIDWIFERY CARE MANAGEMENT FOR A TWO-YEAR-OLD CHILD WITH TUBERCULOUS MENINGITIS - Zebua, Gloria Elza; Lumbantoruan, Nora C; Pardosi, Sri Juwita Stefany; Simamora, Lasria; Irmayani, Hilda (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Tuberculous meningitis is a severe form of extrapulmonary tuberculosis that commonly affects children under five years of age and may lead to serious neurological complications, disability, or death if not managed appropriately. Objective: This study aimed to describe the implementation of midwifery care management for a two-year-old child diagnosed with tuberculous meningitis in the Pediatric Intensive Care Unit (PICU) of Haji General Hospital Medan, North Sumatra Province, in 2025. Methods: A case study design was employed using Varney’s seven-step midwifery management framework, including data collection, data interpretation, identification of actual and potential problems, immediate interventions, care planning, implementation, and evaluation. Data were obtained through observation, physical examination, medical records, and collaboration with the healthcare team. Results: Assessment findings showed decreased consciousness, respiratory distress, a history of seizures, muscle rigidity, and dependence on mechanical ventilation. Midwifery interventions focused on neurological and respiratory monitoring, airway maintenance, ventilatory support, vital sign assessment, fluid balance monitoring, and multidisciplinary collaboration. Evaluation indicated stable oxygen saturation, maintained airway patency, absence of recurrent seizures, and improvement in the patient’s overall clinical condition. Conclusion: Comprehensive, systematic, and collaborative midwifery care contributed to patient stabilization, prevention of complications, and improvement of clinical outcomes in a child with tuberculous meningitis treated in the PICU.